(untitled) (Journal of Comparative & International Higher Education, 2022)
Among the leading issues that dominated debate throughout 2020, diversity on higher education campuses surfaced once again demanding change of existing as well as future practices. Addressing and incorporating diversified cultural perspectives require universities to do much more than issuing diversity statements. This research study employed Q-methodology to explore and compare the perspectives that two groups of international and domestic students hold regarding the American model of the research university. The groups included Arab students studying at a public research university in the United States, and domestic American students studying at a public research university in the United States. Fifteen students from both groups—representing a total of 30 participants—were interviewed. Factor analysis indicated that students from both cultural backgrounds held unique perspectives regarding the value of the American model of the research university.